A Survey On The Customer Satisfaction Towards Customer Service In Penang's Cafeteria - Suo, Qiang (2008)
The main purpose of this study was to determine the perception of customer service in Penang's cafeteria and their satisfaction among 108 respondents from different Penang's cafeterias and companies, and across these factors: Quality of the food, Cost/Value of the food, Cafeteria Staff, Atmosphere. The study also investigated differences in customer satisfaction in demographic variables: age and gender. In assessing customer satisfaction, a questionnaire developed by Dallbolkar et.al. (1996) and Reid and Gundlach (1984) was adopted in the research. Statistical tools used were frequency counts, percentages, mean, Pearson's r., T-test and One-Way ANOVA. Analyses were done using the SPSS for Windows (Version 12.0) computer software and set at 0.05 level of significance. The overall customcr satisfaction is "good". In this case quality of food (sig = .042) and the atmosphere of the cafeteria (sig=.039) are the variables that make significant unique contribution towards prediction of the dependent variable. Cost/value of the food (sig=.356) and cafeteria staff (sig=.869) must be improved. They should continue to provide the better service and strive further to improve the quality of service, as service quality can be used as a strategy to gain competitive advantages.